Pathogenic variants in KPTN gene identified by clinical whole-genome sequencing - Thiffault, Isabelle (Cold Spring Harb Mol Case Stud, 2020)
Status epilepticus is not rare in critically ill intensive care unit patients, but its diagnosis is often delayed or missed. The mortality for convulsive status epilepticus is dependent on the underlying aetiologies and the age of the patients and thus varies from study to study. In this context, effective molecular diagnosis in a pediatric patient with a genetically heterogeneous phenotype is essential. Homozygous or compound heterozygous variants in KPTN have been recently associated with a syndrome typified by macrocephaly, neurodevelopmental delay, and seizures. We describe a comprehensive investigation of a 9-yr-old male patient who was admitted to the intensive care unit, with focal epilepsy, static encephalopathy, autism spectrum disorder, and macrocephaly of unknown etiology, who died of status epilepticus. Clinical whole-genome sequencing revealed compound heterozygous variants in the KPTN gene. The first variant is a previously characterized 18-bp in-frame duplication (c.714_731dup) in exon 8, resulting in the protein change p.Met241_Gln246dup. The second variant, c.394 + 1G > A, affects the splice junction of exon 3. These results are consistent with a diagnosis of autosomal recessive KPTN-related disease. This is the fourth clinical report for KPTN deficiency, providing further evidence of a wider range of severity.